Assistance in reporting individual tax returns after the tax incentive policy in the midst of the Covid-19 pandemic - Nandiroh, Umi; Hariri, Hariri (Community Empowerment)
The tax incentive policy in the midst of the Covid-19 pandemic has had an impact on changing the way the year-end tax calculation and annual tax returns are filled out. In fact, many taxpayers do not understand how to calculate and report annual taxes. Therefore, this community service is intended to provide solutions to the difficulties experienced by taxpayers, through assistance in reporting individual tax returns after tax incentive policies. This activity is entitled 'TC Mengabdi'. TC Mengabdi recruits Unisma Faculty of Economics and Business students with certain criteria. TC Serving members are selected and briefed according to the standards of the Directorate General of Taxes, before being given field assignments to provide socialization and education to taxpayers. The TC Serving team is stationed at KPP Batu and the Unisma Tax Center. This activity has served and assisted around 4,000 taxpayers in Malang Raya. Through the TC Serving program, taxpayers are greatly assisted in fulfilling their tax obligations, starting from calculating, paying, and reporting taxes.